Simulation of thermodynamic aspects of AI-Si binary system - Saheb Nouari,; Abdul Razak Daud,; Redzuwan Yahya,; Shahidan Radiman, (Universiti Kebangsaan Malaysia, 2002)
It is possible to perform a thermodynamic analysis to a system by using thermodynamic models for the Gibbs energy of individual phases. As a result a thermodynamic data can be created for each system. The models are phenomenological involving empirical parameters which could be defined or estimated from experimental information. Once the Gibbs energy functions of phases in the system have been obtained, many thermodynamic properties may be calculated by applying standard thermodynamic relations. In the present study Thermo-Calc software was used for plotting the phase diagram of the Al-Si binary system and other property diagrams. A simulation of solidification process was also highlighted.